2008
DOI: 10.1042/cs20070379
|View full text |Cite
|
Sign up to set email alerts
|

Local expression of Toll-like receptor 4 at the site of ruptured plaques in patients with acute myocardial infarction

Abstract: Several reports suggest that a chronic inflammatory process plays a key role in coronary artery plaque instability and subsequent occlusive thrombosis. In a previous study, we found that TLR4 (Toll-like receptor 4) mediates the synthesis of cytokines in circulating monocytes of patients with AMI (acute myocardial infarction); however, it remains unclear whether TLRs are expressed at the site of the ruptured plaque in these patients. The aim of the present study was to determine whether TLR2 and TLR4 are expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 35 publications
3
58
0
Order By: Relevance
“…TLR4 was also increased systematically in patients following myocardial infarction (MI) and locally at site of plaque rupture, yet suggesting that monocyte TLR4 has a role in plaque destabilization and rupture (Ishikawa et al, 2008). TLR4 was increased in both stable and unstable angina, with a congruent increase in TLR2 in the unstable state only (Ashida et al, 2005).…”
Section: Monocyte Activation and The Role Of Toll Like Receptorsmentioning
confidence: 96%
“…TLR4 was also increased systematically in patients following myocardial infarction (MI) and locally at site of plaque rupture, yet suggesting that monocyte TLR4 has a role in plaque destabilization and rupture (Ishikawa et al, 2008). TLR4 was increased in both stable and unstable angina, with a congruent increase in TLR2 in the unstable state only (Ashida et al, 2005).…”
Section: Monocyte Activation and The Role Of Toll Like Receptorsmentioning
confidence: 96%
“…TLR4, whose endogenous ligand is ox-LDL (Xu et al, 2001), is highly expressed in SMC of atherosclerotic vessels, where it has been associated with the induction of a proinflammatory phenotype (Loppnow et al, 2008;Otsui et al, 2007). Furthermore, TLR4 has been found in atherosclerotic lesions and at the site of plaque rupture in patients with MI (Ishikawa et al, 2008), and its expression is increased in thrombi from patients with acute coronary syndromes (Wyss et al, 2010;Yonekawa et al, 2011). Moreover, several studies showed that circulating monocytes of patients with atherosclerotic disease exhibit higher expression of TLR2 and TLR4 as compared to healthy individuals (Geng et al, 2006;Kuwahata et al, 2010;Mizoguchi et al, 2007;Shiraki et al, 2006), and an enhanced TLR signaling has been demonstrated in monocytes of patients with ACS (Ashida et al, 2005;Versteeg et al, 2008).…”
Section: Toll Like Receptors As Link Between Inflammation and Metabolmentioning
confidence: 99%
“…21 Together these cells orchestrate local mobilization of monocytes in reparative processes in response to the ischemia and inflammation which is seen in ACS. 22 Plasma MCP-1 levels increase as early as 3 hours after the onset of chest pain, reach their maximum at 24 hours, and remain elevated for at least 7 days. 23 Interestingly, the majority of studies on MCP-1 genetic polymorphism failed to find any association with the risk of MI (supplemental Table III).…”
Section: Monocyte-endothelium and Monocyte-myocardial Interactionsmentioning
confidence: 99%